Teaching for student learning : becoming an accomplished teacher - Arends, Richard (Routledge, 2010)
Shows teachers how to integrate research and the wisdom of practice into their teaching, emphasizing how accomplished teachers acquire and apply evidence-based practices in support of student learning.